Circulating concentrations of soluble L-selectin (CD62L) in patients with primary Sjögren's syndrome. Issue 4 (1st April 2000) - García-Carrasco, Mario; Pizcueta, Pilar; Cervera, Ricard; Ramos-Casals, Manuel; Sisó, Antoni; de la Red, Gloria; Ingelmo, Miguel; Font, Josep; Engel, Pablo
Abstract : OBJECTIVE: Serum concentrations of soluble (s) L-selectin (CD62L) were measured in patients with primary Sjögren's syndrome (SS) to relate these concentrations to clinical and immunological features of SS. METHODS: The study included 40 consecutive patients (38 women and two men) with a mean age of 61 years (range 24–78) who fulfilled four or more of the preliminary diagnostic criteria for SS proposed by the European Community Study Group in 1993, and 33 healthy blood donors from the hospital blood bank. A sandwich enzyme linked immunosorbent assay (ELISA) was used to detect the soluble form of human sL-selectin (CD62L). RESULTS: The mean (SEM) values of sL-selectin (CD62L) were 861 (66) μg/ml for patients with SS and 986 (180) μg/ml for healthy blood donors, but there was no significant difference. In patients with primary SS, serum sL-selectin (CD62L) concentrations were significantly higher in patients with Raynaud's phenomenon (1275 (112) μg/ml versus 789 (69) μg/ml, p=0.007), autoimmune thyroiditis (1162 (113) μg/ml versus 787 (69) μg/ml, p=0.02) and rheumatoid factor (993 (95) μg/ml versus 684 (70) μg/ml, p=0.01) when compared with patients without these features. CONCLUSION: The presence of Raynaud's phenomenon, autoimmune thyroiditis and rheumatoid factor is associated with higher concentrations of circulating sL-selectin (CD62L) in the sera of patients with primary SS.